ANALISIS UNSUR MODAL SOSIAL TERHADAP PRODUKTIVITAS PETANI RUMPUT LAUT DI KECAMATAN SUPPA KABUPATEN PINRANG - Irmayani Irmayani; Nur Rahmah Safarina Hamzah; Yusriadi Yusriadi; Adimah Amrawaty; Rahmadani Rahmadani (Jurnal AGRIBIS, 2022)
Social capital refers to the strength of social relationships among the society which directly affects the productivity and wealthy of the society. This research focuses on certain Social capitals such as: participation in a network, reciprocity, and proactive action. The objective of this research are to determine what social capitals are implemented by the farmenrs and its effect towards the productivity of the seaweed in Suppa Pinrang. This research applied Qualitative-Quantitative research design. Qualitative method is administered to measure the social capital while the Quantitative to explain the productivity of the farmers. The result shows that the strongest social capital is Reciprocity and the others social capital are also positively affect the productivity of the seaweed at Suppa PinrangÂ Keywords: Social capital; farmer; productivity of seaweed